Bevacizumab as adjuvant therapy for recurrent respiratory papillomatosis in an infant. (February 2020) - Gates, Christopher; Tomboc, Patrick; Allison, Andrew; Carr, Michele
Abstract: Recurrent Respiratory Papillomatosis (RRP) is a benign disease of the airway that can result in symptoms ranging from mild dysphonia to respiratory distress to respiratory failure related to colonization of the lung parenchyma. It is a disease that typically begins in childhood and can require treatment indefinitely, though may remit in adolescence. Although treatment includes surgical management, certain cases require adjuvant therapy. Many therapies have been tried over the years with varying levels of success. Our patient presented as a 7 month old male in respiratory distress, who was subsequently diagnosed with RRP. He has required a tracheostomy, ventilation, and frequent surgical debridement for the last 20 months. Due to the aggressiveness of his disease, he was started on systemic bevacizumab (Avastin) in an effort to stabilize his lesions. Though early effect seemed apparent based on Derkay scores, systemic bevacizumab has failed to elicit clinical improvement in our patient. He remains with a tracheostomy receiving bevacizumab 10 mg/kg as an intermittent infusion approximately every 4 weeks along with surgical debridement with little to no clinical improvement thus far. In light of the recent successes with bevacizumab therapy, this case highlights the difficulty in finding new treatment for this disease.